2018
DOI: 10.1371/journal.pone.0195436
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of human recreation on carnivores in protected areas

Abstract: Mammalian carnivores can be particularly sensitive to human disturbance, even within protected areas (PAs). Our objective was to understand how human disturbance affects carnivore communities in southern Arizona, USA by studying habitat occupancy based on data collected using non-invasive methods in three PAs with different levels of human disturbance. Carnivore occupancy varied based on human disturbance variables (i.e., roads, trails, etc.). Common carnivore species (coyotes, gray foxes, and bobcats) had hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 67 publications
(93 reference statements)
1
18
1
Order By: Relevance
“…In the HWS, instead, we documented the presence of tigers, and we also know that leopards are commonly present [ 26 , 59 ]. This result suggests a possible effect of human disturbance on large carnivores in the RYER, as already documented in many other areas of the world [ 60 , 61 , 62 , 63 ]. Certainly, this fact highlights the importance of focusing conservation efforts on this threatened group because human–large carnivore conflict is one of the main reason of the decline of this group worldwide [ 64 ], especially for tigers [ 65 ].…”
Section: Discussionsupporting
confidence: 75%
“…In the HWS, instead, we documented the presence of tigers, and we also know that leopards are commonly present [ 26 , 59 ]. This result suggests a possible effect of human disturbance on large carnivores in the RYER, as already documented in many other areas of the world [ 60 , 61 , 62 , 63 ]. Certainly, this fact highlights the importance of focusing conservation efforts on this threatened group because human–large carnivore conflict is one of the main reason of the decline of this group worldwide [ 64 ], especially for tigers [ 65 ].…”
Section: Discussionsupporting
confidence: 75%
“…Another feature of human‐influenced landscapes is disturbance, such as vehicular traffic and walking safaris. Disturbance can result in the modification of behavioural patterns and individual performance of large mammals (Baker & Leberg, 2018; Caro, 1999; Frid & Dill, 2002; Pépin, Lamerenx, Chadelaud, & Recarte, 1996) by imposing limitations to movement (Klar, Herrmann, & Kramer‐Schadt, 2009), affecting mating opportunities (Frair, Merrill, Beyer, & Morales, 2008; Leblond, Dussault, & Ouellet, 2013), modifying foraging routes (Leblond et al., 2013) or increasing perceived predation risk (Frid & Dill, 2002). Both spatial and temporal changes have been recorded, for example large‐bodied mammals avoiding roads (Mohd‐Azlan et al., 2018) or animals being active when humans are absent (Gaynor, Hojnowski, Carter, & Brashares, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have therefore aimed at assessing the effects of outdoor recreational activities on wildlife (Steidl and Powell, 2006;Steven et al, 2011;Gutzwiller et al, 2017). Effects of trails, mainly through generating edge habitat, have been substantially investigated (Marini et al, 1995;Dale et al, 2000;Flaspohler et al, 2001) as well as considering the effect of the mere presence of humans, in or outside protected areas (Müllner et al, 2004;Arlettaz et al, 2007;Martin and Réale, 2008;Kangas et al, 2010;Rösner et al, 2014;Bötsch et al, 2017;Baker and Leberg, 2018). Studies investigating trail effects on birds found inconsistent results, with some studies showing an effect of trails while others do not (Gutzwiller et al, 1998;Miller et al, 1998;Deluca and King, 2014;Thompson, 2015).…”
Section: Introductionmentioning
confidence: 99%